Development of cell-to-cell balancing circuit for lithium-ion batteries - Wong, Wei Jun (2024)
This study provides a thorough investigation into the design and evaluation of a single switch capacitor active balancer prototype designed for lithium-ion batteries. Additionally, it explores both hardware testing and software simulations, with the main goal of examining its effectiveness in different operational modes, such as stationary, charging, and discharging conditions. The hardware evaluation revealed promising results of approximately 80% and 30% improvement compared to situations without balancer during the stationary and charging phases to demonstrate significant balancing effects, indicating that the prototype can reduce voltage variations between cells to 0.1 V. On the other hand, the balancer's performance showed clear limitations when discharging, indicating a gap in its effectiveness under operating circumstances between charging and discharging conditions. Software simulations, on the other hand, generated more promising results, suggesting possible capability under all three circumstances and evaluating balancing efficiency using indicators like standard deviation and percentage difference. Interestingly, more comparison with prototypes created by other final year project students showed a repeated trend in which balancers primarily demonstrated their effectiveness only in the stationary and charging phases, similar to the difficulties in getting stable balancing performance over a battery's lifetime.